Global Marketing: Importance of Human Resource and Supply Chain Risk Management to Build a Successful Company from Global Marketing Perspective - Thian Sheung, Chia; Yazdanifard, Rashad (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
Global markets are expanding rapidly. The term global marketing has been in use only since the 1980s. Before that decade, international marketing was the term used most often to describe marketing activities outside one’s domestic market. Global marketing is not just a new label for an old phenomenon; however, it also provides a new vision for international marketing. This paper mainly examines the organization’s internal management to coordinate their work and achieve certain goals or targets. This paper not only illustrates the challenges of developing and upholding strong trust in global human resource management from global marketing perspectives, but also the challenges that highlight how global marketers manage their global supply chain risk management. While global marketers comprises of members across different locations, cultures, and time, the highlighted challenges are overcome via two communication behaviours, such as cross-cultural communication and computer-mediated, which study describes the communication behaviours that might boost trust in global human resource management which may lead company to success. In today’s increasingly complex environment, risk adjusted supply chain management also focused in this research which can drive into improved ﬁnancial performance and competitive advantage.